Pelatihan Penggunaan Repetition Method Berbasis Website untuk Memudahkan Guru dalam Melatih Daya Ingat Peserta Didik - Syahrial, Syahrial; Alirmansyah, Alirmansyah; Asrial, Asrial; Suhartini, Sugih; Faizal, Faizal (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
The training on the use of website-based learning methods in elementary schools still faces several challenges, particularly due to teachers’ limited ability to use digital technology to enhance students’ memory retention. This study aims to implement training on website-based expansion methods as a tool to help teachers optimize learning strategies so that the material becomes easier for students to remember at SDN 80/1 Muara Bulian. Using a descriptive qualitative approach, the study involved several teachers and collected data through observation, interviews, and documentation during the training activities. The results showed that the training helped teachers design digital activities, organize interactive materials systematically, and increase student engagement. The website’s automatic evaluation feature also facilitated teachers in monitoring students’ memory development. Overall, the training proved effective in supporting adaptive, structured, and memory-oriented learning processes.